Advancing into the morphology of female differentiation in the seabob shrimps Xiphopenaeus dincao and X. kroyeri: Insights into the taxonomy - Miazaki, Lizandra F. [UNESP]; França, Nielson F.C.; Nogueira, Caio S. [UNESP]; Mantelatto, Fernando L.; Costa, Rogerio C. [UNESP] (Elsevier, 2024)
Xiphopenaeus shrimps species are among the main marine organisms exploited in commercial fishing in the Americas. Recent investigations have unveiled a species complex formerly identified as X. kroyeri. Within it, two species coexist along the Brazilian southeastern coast: X. dincao and X. kroyeri. However, their identification currently relies on the morphology of adult males, with no available morphological information enabling the identification of females. We employed an integrative approach to explore morphological traits aiding species discrimination using female morphology. Molecular assessments were conducted for these species’ identification. Morphology, morphometry and computerized tomography were employed to examine the usefulness of thelycum morphology in their identification. Conspicuous differences were observed between X. dincao and X. kroyeri. The analyses showed that thelycum is an informative character for their identification, with the main differences being related to the width and shape of the anterior median protuberance. These results fill the information gap concerning the identification of both species and provide greater precision in future research that requires the correct identification of these shrimps.
Keywords: COI; Fishery Resources; Geometric Morphometrics; Nano CT scan; Penaeidae; Thelycum